2021
DOI: 10.1073/pnas.2023157118
|View full text |Cite
|
Sign up to set email alerts
|

ORF10–Cullin-2–ZYG11B complex is not required for SARS-CoV-2 infection

Abstract: In order to understand the transmission and virulence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), it is necessary to understand the functions of each of the gene products encoded in the viral genome. One feature of the SARS-CoV-2 genome that is not present in related, common coronaviruses is ORF10, a putative 38-amino acid protein-coding gene. Proteomic studies found that ORF10 binds to an E3 ubiquitin ligase containing Cullin-2, Rbx1, Elongin B, Elongin C, and ZYG11B (CRL2ZYG11B). Since C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 34 publications
1
39
0
Order By: Relevance
“…Compared with the SARS-CoV genome, the SARS-CoV-2 genome uniquely encodes the ORF10 protein, which contains 38 amino acids [ 13 , 14 ]. ORF10 was reported to bind to an E3 ubiquitin ligase complex containing Cullin-2, Rbx1, Elongin B, Elongin C, and ZYG11B, which ubiquitinates host proteins and degrades them via the 26 S proteasome; ZYG11B is dispensable for SARS-CoV-2 infection, and the interaction between ORF10 and ZYG11B is not relevant for SARS-CoV-2 infection [ 15 ]. However, how ORF10 functions in the interaction between the virus and host cells is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the SARS-CoV genome, the SARS-CoV-2 genome uniquely encodes the ORF10 protein, which contains 38 amino acids [ 13 , 14 ]. ORF10 was reported to bind to an E3 ubiquitin ligase complex containing Cullin-2, Rbx1, Elongin B, Elongin C, and ZYG11B, which ubiquitinates host proteins and degrades them via the 26 S proteasome; ZYG11B is dispensable for SARS-CoV-2 infection, and the interaction between ORF10 and ZYG11B is not relevant for SARS-CoV-2 infection [ 15 ]. However, how ORF10 functions in the interaction between the virus and host cells is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The per-residue disorder profiles for 138 unique SARS-CoV-2 ORF10 variants (vari- Here, we investigate the effects of point mutations on the overall disorder score for in ORF10 to target it for degradation [32,33].…”
Section: Intrinsic Disorder Regions Of Sars-cov-2 Orf10 Variants 173mentioning
confidence: 99%
“…The SARS-CoV-2 ORF10, a putative 38-amino acid viral protein encoded in the 3′ accessory region of the genome, is a highly ordered, hydrophobic, and thermally stable protein, which contains at least one transmembrane region [34] , [35] . The ORF10 binds to components of a Cullin-2-RING-ligase (CRL2) complex containing Cullin-2, RBX1, Elongin B, Elongin C, and ZYG11B ( CRL 2 ZY G 11 B ) [36] , [37] , [38] . Earlier, it has been reported that the extreme N terminus of ORF10 contains a methionine-glycine-tyrosine motif, which would presumably aid ORF10 to be recruited into the CRL 2 ZY G 11 B ubiquitin ligase complex [37] .…”
Section: Introductionmentioning
confidence: 99%
“…The ORF10 binds to components of a Cullin-2-RING-ligase (CRL2) complex containing Cullin-2, RBX1, Elongin B, Elongin C, and ZYG11B ( CRL 2 ZY G 11 B ) [36] , [37] , [38] . Earlier, it has been reported that the extreme N terminus of ORF10 contains a methionine-glycine-tyrosine motif, which would presumably aid ORF10 to be recruited into the CRL 2 ZY G 11 B ubiquitin ligase complex [37] . It was further confirmed that interaction between ORF10 and CRL 2 ZY G 11 B is not relevant for SARS-CoV-2 infection in vitro [37] , [39] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation